The Romanovs in the Caucasus through the lens of written sources of the 19th to the early 20th centuries - Petr A. Kuzminov; Alina M. Sherieva (Кавказология)
The article discusses the visits of representatives of the Romanov dynasty to the Caucasus and their influence on the life and customs of the mountain peoples of the Northern Caucasus. To attain this goal, a combination of legislative, administrative, personal history sources, and information from periodicals were used. Each type of historical source helped shed light on the unique nature of these relationships, highlighting their significance for both the Romanovs and the mountain peoples. Legislative sources allowed for the detailed examination of agrarian reforms, showing that despite Alexander II’s assertion of projects to grant land to the mountaineers, and thus becoming law for all subjects of the Russian Empire, under pressure from the mountaineers who identified many flaws in these projects, the government was forced to reconsider the results of the reform and make significant amendments to the final version of landownership and land use in the Northern Caucasus. The memoirs of S. Siukhov depict one of the most tragic episodes of the Caucasian War: the meeting of Emperor Alexander II with representatives of the Adyghe peoples, which ended in a new confrontation. The majority of Adyghe society chose departure to Turkey over relocation to the plains. Administrative sources described Alexander III’s meeting with representatives of the Kabardian and Balkar peoples, which resulted in the granting of alpine meadows to mountaineers.